2017
DOI: 10.1016/j.energy.2017.05.148
|View full text |Cite
|
Sign up to set email alerts
|

Estimating energy savings from benchmarking policies in New York City

Abstract: A growing number of governments have begun to implement benchmarking or energy disclosure policies. By requiring owners to measure and disclose their energy use, these policies are intended to transform the market for energy-efficient investments in existing buildings. To improve future policy efforts, two critical questions are: first, how much energy do these policies save? and second, what particular aspects of these policies are most effective? To answer these questions, this study explores how different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 28 publications
0
24
1
2
Order By: Relevance
“…Our result is different from the one obtained by Meng et al (2017). After applying a novel difference-in-difference strategy, they conclude that in the fourth year of policy implementation, the disclosure of Energy Star Scores to the public decreased the source EUI by 12.9%, when controlling for other key building features.…”
Section: Limitationscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our result is different from the one obtained by Meng et al (2017). After applying a novel difference-in-difference strategy, they conclude that in the fourth year of policy implementation, the disclosure of Energy Star Scores to the public decreased the source EUI by 12.9%, when controlling for other key building features.…”
Section: Limitationscontrasting
confidence: 99%
“…However, their study failed to prove actual causality between the policy and the decrease. To date, various other studies have also shown conflicting results as to the effectiveness of benchmarking policies (Meng, Hsu & Han, 2017). Nevertheless, in 2016, New York City expanded their benchmarking and disclosure requirement to include buildings over 25,000 feet with Local Law 133.…”
Section: Introductionmentioning
confidence: 99%
“…Primary energy is the raw fuel that is burned to create heat and electricity, such as natural gas or fuel oil used in on-site generation. Secondary energy is the energy product (heat or electricity) created from a raw fuel, such as electricity purchased from the grid or heat received from a district steam system [35].…”
Section: Source-site Ratio and Energy Use Intensitymentioning
confidence: 99%
“…Some cities also have requirements for energy audits or building tune-ups. While benchmarking and audits do not inherently require energy-use reductions in and of themselves, the premise is that requiring information disclosure will prompt action by building owners and operators, as evidenced by some studies (Meng et al 2017;Palmer & Walls 2017;Kim & Lim 2018;Gui & Gou 2020). A study of New York City's mandatory audit policy found reductions of 2.5% for multifamily and 4.9% for office buildings, suggesting that audits create an insufficient incentive to invest in energy efficiency at the level needed to meet the city's GHG reduction goals (Kontokosta et al 2020).…”
Section: Introductionmentioning
confidence: 99%